2020
DOI: 10.1105/tpc.19.00542
|View full text |Cite
|
Sign up to set email alerts
|

ARGONAUTE2 Enhances Grain Length and Salt Tolerance by Activating BIG GRAIN3 to Modulate Cytokinin Distribution in Rice

Abstract: Optimizing cytokinin distribution patterns is a promising strategy for simultaneously enhancing grain yield, grain quality, and stress resistance in plants, as observed in ARGONAUTE2-overexpressing rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 68 publications
0
54
0
Order By: Relevance
“…However, no data suggesting that PUP14 is involved in systemic transport have been reported. In rice, BIG GRAIN3 , the encoding plasma membrane‐localized OsPUP4, has been characterized as a gene that modulates the distribution of cytokinins in the shoots and roots (Xiao et al ., 2019; Yin et al ., 2020). However, direct evidence in systemic transport has not been provided.…”
Section: Abcg14 and Pup14 Play Different Roles In Cytokinin Transportmentioning
confidence: 99%
“…However, no data suggesting that PUP14 is involved in systemic transport have been reported. In rice, BIG GRAIN3 , the encoding plasma membrane‐localized OsPUP4, has been characterized as a gene that modulates the distribution of cytokinins in the shoots and roots (Xiao et al ., 2019; Yin et al ., 2020). However, direct evidence in systemic transport has not been provided.…”
Section: Abcg14 and Pup14 Play Different Roles In Cytokinin Transportmentioning
confidence: 99%
“…In addition to cytokinin content, the distribution of cytokinin may be an important factor affecting plant salt tolerance. Yin et al [112] showed that overexpression of ARGONAUTE2 (AGO2) in rice can decrease cytokinin content in shoots and increase cytokinin content in the roots, leading to increased salt tolerance and grain length of rice under salt stress. AGO2 affects the distribution of cytokinin by promoting the expression of BIG3 (GRAIN3), which encodes a protein that may be involved in cytokinin transport, and AGO2, which changes the histone methylation level of BG3.…”
Section: Salt Stress Responsementioning
confidence: 99%
“…It has been shown that CKs also promote grain size and grain number in rice ( Ashikari et al, 2005 ; Gao et al, 2014 ; Xiao et al, 2019 ; Yin et al, 2020 ). To test whether the decrease of grain size and grain number in OsPUP1 -overexpressing plants are associated with the alteration of CK content, we further quantified the CK content in the panicles ( Figures 3E,F and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further efforts uncovering this complicated system are significant for understanding hormone functions in plant growth and development. Given the crucial roles of the OsPUP1 as well as OsPUP4 and OsPUP7 in regulating several key agronomic traits, comprehension of the hormone transport certainly has a great potential for crop improvement as has been exemplified in a recent study ( Yin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%